C–H···π(metal–ligand ring) interaction in a mesaconate bridged Cd(II) 1-D coordination polymer: structural elucidation, theoretical study, and photophysical properties. Issue 7 (2nd April 2020) - Alothman, Zeid Abdullah; Dutta, Basudeb; Alam, Seikh Mafiz; Wabaidur, Saikh Mohammad; Mir, Mohammad Hedayetullah
Abstract: A Cd(II)-based one-dimensional coordination polymer (1-D CP), [Cd2 (mes)2 (4-phpy)4 ] (1 ), was prepared using mesaconic acid (H2 mes) and 4-phenyl pyridine (4-phpy) mixed ligand system. Compound 1 has been characterized by elemental analysis, infrared spectroscopy, thermogravimetric analysis (TGA), powder X-ray diffraction (PXRD) pattern and single crystal X-ray diffraction (SCXRD) techniques. Structural elucidation reveals a 1-D chain which contains a 14-membered metal-ligand ring composed of two mes ligands and two Cd(II) centers. Further, the 1-D chains are assembled into a two-dimensional (2-D) supramolecular network by C–H···π(metal-ligand ring) interactions. The fluorescence lifetime of 1 shows a good range of average lifetime. The theoretical band gap has also been calculated by density functional theory (DFT) computations, which shows that 1 may possess semiconducting properties. Graphical Abstract: